Analysis of Short Story Writing Ability of Grade 5 Students in Elementary School - Nurlela; Iswara, Prana Dwija (International Conference on Elementary Education, 2025)
Currently, the flow of globalization is increasingly rapid, as well as the development of abilities in the 21st century that require communication skills, critical thinking, creative thinking and collaboration. One form of creative thinking is the ability to write. There are many types of writing. In this study, the aim is to analyze the ability to write short stories of 5th grade students in elementary schools. This study uses a qualitative descriptive method, with subjects being 5th grade students of one of the X state elementary schools in West Bandung Regency, totaling 23 students. The data collection technique used is observation and literature review. Through data collection in the form of student writing, this study will identify students’ strengths and weaknesses in writing short stories. The aspects analyzed include story structure, content, language, spelling and punctuation and creativity. in developing story ideas. Based on the results of data analysis, the ability to write short stories that fall into good qualifications is 2 students (8.7%). The ability to write short stories with sufficient qualifications is 6 students (26.1%). The ability to write short stories with less qualifications is 15 students (65.2%). In accordance with the calculation of the average score, it can be concluded that the ability to write short stories of class 5 students at one of the state elementary schools in West Bandung Regency with an average score of 1.9 falls into the low qualifications.